Memahami Sikap dan Perilaku Pelanggan Terhadap Layanan Pengiriman Makanan Dengan Menggunakan Online Food Delivery (OFD) : Investigasi Motivasi dan Tantangan Pelanggan - Puspasari, Aulia Putri Mega; Eka Putri, Seprianti (Universitas Islam Kadiri, 2023)
The rise of food services using Online Food Delivery (OFD) is very significant due to its ability to deliver food quickly thereby increasing effectiveness. Therefore, this research tries to understand consumers' desires and intentions to adopt OFD through behavioral reasoning theory. The iui research was conducted using data from 202 OFD users in Indonesia through an online survey. The quantitative method was chosen using the SEM (Structural Equation Modeling) data analysis technique using the PLS (Partial Least Squares) software application. Research proves that From a managerial perspective, research findings validate the impact of all constructs on consumer desires and behavioral intentions